System level simulation and fabrication of SOI-MEMS differential Capacitive accelerometer - Veena.S; H.L Suresh; Newton Rai; Veerapandi N; Veda Sandeep Nagaraj (Journal of Applied Science and Engineering, 2024)
This study primarily covers the design and development of an MEMS based accelerometer. Frequency, displacement sensitivity, and capacitance are the subject of analytical modelling; the corresponding values are found to be 7.41kHz, 4.5096∗10−9 m/g, and 0.289pF respectively. COMSOL Multiphysics is used to design the structure of accelerometer and the MATLAB simulator tool is used to analyse the accelerometer. In order to obtain precise results, simulations are done and theoretical calculations are compared. Silicon-on-Insulator Multi-User MEMS Processes (SOIMUMPS) technology is employed to fabricate the accelerometer structure at MEMSCAP foundry, United State. The characterization of the fabricated device is done at CENSE, IISc, Bangalore. The capacitance values on either side of the device obtained from the test results are 0.36pF and 0.85pF when 5 V is applied to the electrodes. The proposed accelerometer is employed in the actuating parts of the sensor due to its properties like linearity and low sensitivity.